Diversification Strategies in Private School Marketing: Efforts to Increase Competitiveness in the Digital Era - Miswari Miswari; Mufidah Mufidah; Ulil Albab Al Aulia Alpaten (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This research analyzes the implementation of diversification-based marketing strategies at SMP Muhammadiyah 8 Mijen Semarang as an effort to increase the attractiveness and sustainability of the institution in the midst of intense competition. The method used is a descriptive case study with a qualitative approach, integrating primary data through interviews and observations, as well as secondary data in the form of internal school documents. The findings show that product diversification such as the Muhammadiyah Boarding School (MBS) program, STEM, and bilingual classes are superior strategies, but have not been supported by optimal digital promotion and adequate community involvement. Key barriers include the lack of social media interaction, alumni participation, and integrated promotion evaluation. Recommendations include optimizing digital marketing, increasing community engagement, and leveraging alumni networks as school ambassadors. This study provides practical and academic insights into the importance of adaptive marketing management for private educational institutions.